2020
DOI: 10.1186/s12911-020-01183-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of real-world data on growth hormone therapy adherence using a connected injection device

Abstract: Background Poor adherence to long-term recombinant human growth hormone (r-hGH) treatment can lead to suboptimal clinical outcomes; consequently, supporting and monitoring adherence is a crucial part of patient management. We assessed adherence to r-hGH treatment in children with growth disorders over 48 months using a connected monitoring device (easypod™), which automatically transmits adherence data via an online portal (easypod™ connect); both sit within an adherence decision support system (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…The data captured in the easypod™ ecosystem database currently include longitudinal records for 13,553 children transmitting data on > 10 injections from January 2007 to February 2019 [ 29 ]. The 10 injection cut-off point was imposed to exclude test or training injections from when therapy is initiated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data captured in the easypod™ ecosystem database currently include longitudinal records for 13,553 children transmitting data on > 10 injections from January 2007 to February 2019 [ 29 ]. The 10 injection cut-off point was imposed to exclude test or training injections from when therapy is initiated.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of results from the overall database [ 24 ] and separate analyses of data from ECOS [ 23 ] suggest that pubertal children, especially boys, are at greater risk for suboptimal adherence and may benefit from closer engagement, particularly around the age when they start to take responsibility for their injections [ 24 , 28 , 29 ]. Specifically, analyses of data from 9,314 records from the overall database showed that, at each time point studied, a significantly greater proportion of female patients had high adherence (defined as ≥ 85% [medium: > 56% to < 85%; low: ≤ 56%]) than male patients (2849 of 3867 [74%] vs 3879 of 5447 [71%]; P < 0.001) [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…1. Mean dose adherence over the duration of use (injected vs prescribed in %) categorized into optimal (≥85%) or suboptimal (<85%) [7] (this is a reference threshold for adherence and corresponds to approximately one missed injection/week [8]); 2. Persistence of use, defined as the time in years between the first injections and the last recorded injection in the system; patients were considered to have stopped the use if they had no injection recorded for 6 consecutive months; and 3.…”
Section: Data and Feature Engineeringmentioning
confidence: 99%
“…This enables the collection of real-world data on patients and their injection behavior and, hence, the accurate estimation of key treatment-related parameters. While several studies have shown the impact of clinical features on key r-hGH treatment success metrics [6,7], to our knowledge, none has investigated whether engagement with the treatment per se has a positive impact.…”
Section: Introductionmentioning
confidence: 99%
“…Physicians’ knowledge may be limited, which can often lead to delayed referral and diagnosis, and the small number of patients creates difficulties in collection of data to generate large and meaningful data sets unless performed on an international scale. The collection of adherence data is of crucial importance [ 21 ] to optimizing adherence and improving adult height [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%